La perspectiva artística de la publicidad - Barbosa Sánchez, Alma Patricia (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2007)
An interesting aspect of the Mexican public art, from the sixties and until present time, is the ideological debate concerning the hegemónic advertising of the political system and of the advertising companies. From the streets of Mexico City, the Political Graph of the student movement of 968 questioned the authoritarianism of the government system constituting artistic advertising. In the same way, the artistic works of Lorena Wolffer and Saúl Villa questioned the invasion of the public space and the sexist representation of women in commercial advertising.The artists have used the graph as collective reflection, social critic and alternative advertising.